RELASI KERJA SAMA PEMERINTAH DAN KOMUNITAS PUBLIK DALAM PENGELOLAAN MUSEUM KONFERENSI ASIA AFRIKA DI KOTA BANDUNG - Rhesa Anggara Utama (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2024)
This research is about the relationship between the government and the public community in managing the museum. This study seeks to uncover cooperative relationship between the government and the public community to achieve a goal that leads to the quality of museum management, the Museum of the Asian-African Conference in Bandung City. This study uses a qualitative method, determination of informants is done based on criteria, where data collection uses in-depth interviews, observation, and documentation techniques. The results showed that the government's cooperative relations through the Technical Implementation Unit (UPT) of the Directorate of Public Diplomacy of the Ministry of Foreign Affairs of the Republic of Indonesia and the public community through the Friends of the Asia-Africa Museum had been carried out with an equal position as an active partner. The collaboration contributed positively to increasing visit participation and interest in the community at large from year to year, as well as presenting positive responses from various parties through cooperative relationships that can be used as pilot models in the context of museum management in other areas. This study concludes that the practice of cooperative relations between the government and the public community in managing the Asia-Africa Conference Museum is considered not running optimally, which is closely related to the limitations of human resources, budget, and facilities that support the journey of cooperation. Therefore, it is recommended that the cooperative relations that have been going on continue to be developed and continuously improved.